Economic growth, institutional factors and foreign direct investment in selected countries - Kazemi, Morteza (2015)
This dissertation consists of three essays, all of which are empirical assessments of issues related to foreign direct investment (FDI). The first objective of this study is to examine the role of democracy in moderating the growth-effect of FDI. A sample of 87 countries for the 1981-2010 period is employed to test the hypothesis. Using a generalized method of moments (GMMs) panel estimator, the results indicate that FDI by itself has no direct (positive) effect on output growth. However, its interaction with democracy in the host country is found to be important for output growth. This suggests that the marginal impact of FDI on growth is increasing in the level of democracy such that countries with higher level of democracy gain more from multinational enterprises (MNEs) presence. This finding is consistent with the view that host country should have the ability to absorb and internalize new technology associated with FDI inflows. We consider this is an important result as it suggests that democracy is an important element of the nation's absorptive capacity. Therefore, policymakers should weigh the cost of policies aimed at attracting FDI versus those that seek to improve the level of democracy. The second objective of this study is to evaluate the impact of outward FDI on domestic output of East Asian economies. It focuses on the outward FDI from eight East Asian economies (i.e. Hong Kong, Indonesia, Malaysia, the Philippines,Singapore, South Korea, Taiwan, and Thailand) to three advanced countries namely Japan, the United States, and the United Kingdom. The analyses were carried out using both aggregate and disaggregate data. The result using aggregate data reveal that there is no evidence to support the idea that outward FDI is growth-enhancing. However, the results based on disaggregate data to each of advanced countries shows that only outward FDI to the United States are found to be important for the East Asian economies. Meanwhile, investments in Japan and the United Kingdom do not appear to have any positive impact. Accordingly, the results derived from this study suggest that only economic cooperation in the forms of free trades agreement (FTA) or an economic partnership (EP) with the United States has actually benefited East Asian economies. Finally, the third objective of this study is to test the simultaneous role of economic freedom and democracy in attracting FDI inflows. In order to test the hypothesis, data from a sample of 87countries over the period of 1981-2010 is employed. The main finding shows that the influence of economic freedom on FDI inflows is positive and significant. However, the results suggest that the democracy has no significant impact on the FDI inflows. The findings indicate that there is no evidence to support the idea that simultaneous occurrence of economic freedom and democracy are required to attract MNEs presence. Instead, the results reveal that improvement in economic freedom alone is sufficient to attract more FDI inflows. This finding is not consistent with Friedman‘s view that free markets and political freedom are inseparable. Obviously, MNEs respond only to improvement in freedom of economic activity but not the level of democracy.